2016
DOI: 10.1111/cfs.12269
|View full text |Cite
|
Sign up to set email alerts
|

Who returns home? Study on placement outcomes of Flemish foster children

Abstract: Until recently, Flemish family foster care was a temporary measure with as its most important goal, the reunification of the foster child with the birth parents. To date, nothing is known on the number of reunifications, nor has any study been undertaken into the factors (child, parent, foster parent and foster care process) associated with reunification. Case files of 127 foster children who exited foster care in 2007 were analysed. Dependent variables were type of foster care placement outcome (reunification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…In UK studies, the family reunification rate ranged from 31% (Carlson et al, 2020) to 40% (Neil et al, 2020) for all children who were in the care system, whereas it was from 33% (Neil et al, 2020) to 45.6% for children admitted to out‐of‐home care due to maltreatment (Biehal et al, 2015). In studies from other European countries, the reunification rate for children in out‐of‐home care was 52.5% in Sweden (Khoo et al, 2012) and 38.8% for younger children in Denmark (Ubbesen et al, 2012), while for children placed in family foster care, it was 20% in Spain (López et al, 2013), 26% in Belgium (Vanderfaeillie et al, 2017) and 45.1% in Germany (van Santen, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In UK studies, the family reunification rate ranged from 31% (Carlson et al, 2020) to 40% (Neil et al, 2020) for all children who were in the care system, whereas it was from 33% (Neil et al, 2020) to 45.6% for children admitted to out‐of‐home care due to maltreatment (Biehal et al, 2015). In studies from other European countries, the reunification rate for children in out‐of‐home care was 52.5% in Sweden (Khoo et al, 2012) and 38.8% for younger children in Denmark (Ubbesen et al, 2012), while for children placed in family foster care, it was 20% in Spain (López et al, 2013), 26% in Belgium (Vanderfaeillie et al, 2017) and 45.1% in Germany (van Santen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, empirical findings on reunification for other age groups were discordant. There are studies in which the probability of reunification was higher for younger children (López et al, 2013; Murphy & Fairtlough, 2015; van Santen, 2010; Vanderfaeillie et al, 2017), as well as those in which reunification was more likely in older children (Akin, 2011; Esposito et al, 2014; Fernandez et al, 2019; Neil et al, 2020). It should be noted that in some studies, no significant association between the age of the child and reunification was found (Biehal et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to birth parents who sign up their children for adoption, birth parents of foster children can keep the (shared) authority over their children. Sometimes, reunification with the birth parent(s) may follow after placement in a foster family (Burns et al, 2016;Vanderfaeillie et al, 2017). This may imply that foster children have more possibilities to stay connected to their ethnic backgrounds than adoptive children through their birth families, which possibly influences their ethnic identity.…”
Section: Transracial Placements Of Ethnic Minority Children and Ethnic Identitymentioning
confidence: 99%
“…Information may get lost on its way, because foster care workers and guardians do not necessarily share the same vision (Farmer 2012;Vedder et al 2015). Research findings regarding the focus in the reunification process by the child's guardian inconsistently suggest that the focus is mostly on the birth parents' functioning and improvement of their parenting abilities (Arad-Davidzon and Benbenishty 2008; Dankaart 2011), or that the focus is mostly on the child's functioning (Vanderfaeillie et al 2017).…”
Section: The Role and Perspective Of Foster Care Workersmentioning
confidence: 99%